Legal Protection For Victims of Crime Actions of Illegal Access to Personal Information - Rina Arum Prastyanti; S. Andi Sutrasno; Devy Setyani (Proceeding of International Conference on Science, Health, And Technology, 2021)
Illegal access crimes continue to increase from year to year. Accessing information belonging to other people is a violation of human rights, so a legal study is needed to measure how well the Indonesian government is in protecting the interests of its citizens. Especially in the field of technology and information through regulations or government decisions and judges. The objectives to be achieved in this research are: To find out the position of victims of crime in accessing personal information illegally in the Criminal Law justice system. To find out the form of legal protection for victims of crime to access personal information illegally. In this study, the research method used is juridical or normative research methods. This research method uses research on existing library materials to solve problems. The approach method used in this research is to use the statutory regulatory approach. In this study using primary legal materials and secondary legal materials: 1. Primary legal materials are materials that have juridical binding power, such as statutory regulations, court decisions, and agreements. The legal materials used include the Criminal Code. 2. Secondary legal materials are materials that do not have juridical binding power, namely draft laws and regulations, literature, and journals related to the focus of research. Techniques Analysis of the legal materials used in this research is qualitative data analysis including data classification activities in accordance with legal issues and provisions, then editing, presenting the results of the analysis in narrative form, and drawing conclusions. The position of a crime victim in accessing personal information illegally in the Criminal Procedure Code is only as a witness in a criminal case where the victim can only prove the suspect / defendant's guilt. Because in a criminal justice process, the witness (victim) plays a very important role in the effort to reveal a material truth. Legal protection for victims of crime from accessing personal information illegally as part of legal protection to the public, can be manifested in various forms, such as compensation, restitution and compensation. And adhering to the provisions of Law Number 11 of 2008 concerning Information and Electronic Transactions and the Criminal Code.